Performance characteristics and reliability assessment of self-excited induction generator for wind power generation - Varshney L.; Vardhan A.S.S.; Vardhan A.S.S.; Kumar S.; Saket R.K.; Sanjeevikumar P. (My University, 2025)
The paper presents the performance analysis-based reliability estimation of a self-excited induction generator (SEIG) using the Monte-Carlo simulation (MCS) method with data obtained from a self-excited induction motor operating as a generator. The global acceptance of a SEIG depends on its capability to improve the system's poor voltage regulation and frequency regulation. In the grid-connected induction generator, the magnetizing current is drawn from the grid, making the grid weak. In contrast, in the SEIG stand-alone operation, an external capacitor arrangement is implemented to render the reactive power support. This capacitor arrangement is connected across the stator terminals during the stand-alone configuration of SEIG. The capacitor serves two purposes, which include voltage build-up and power factor improvement. Therefore, the paper deals with obtaining the minimum capacitor value required for SEIG excitation in isolated mode applications, including stand-alone wind power generation. The SEIG performance characteristics have been evaluated for different SEIG parameters. The simulation and experimental results are then compared and found satisfactory. Then, SEIG reliability is estimated considering the MCS method utilizing SEIG excitation's failure and success rates during experimental work in the laboratory. Finally, the SEIG reliability evaluation is performed considering different wind speeds. © 2021 The Authors. IET Renewable Power Generation published by John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology.